KRISIS INTEGRITAS DALAM ETIKA PROFESI HUKUM:STUDI KASUS SUAP HAKIM PN SURABAYA (Causa: Jurnal Hukum dan Kewarganegaraan, 2025)
The integrity crisis in the legal profession in Indonesia has become a serious concern, especially after the revelation of a bribery case involving three judges at the Surabaya District Court in the case of the acquittal of defendant Ronald Tannur. This study aims to examine the forms of violations of ethics and the code of ethics of the legal profession that occurred, their impact on the integrity of the justice system and public trust, and prevention efforts so that similar cases do not recur. The study uses a normative legal method with a literature study approach, analyzing relevant primary and secondary legal sources. The results of the study indicate that violations in the form of accepting bribes, conflicts of interest, and abuse of authority have damaged the principles of justice, independence, and integrity of the judiciary. The negative impacts that arise include decreasing public trust, weakening the legitimacy of judicial institutions, and increasing the potential for systemic corruption. Strict enforcement of the code of ethics, strengthening internal and external oversight mechanisms, and structural reform in the judicial system are strategic steps needed to restore the integrity and professionalism of law enforcement officers in Indonesia, while strengthening the foundation of independent and integrated justice for the wider community. Krisis integritas dalam profesi hukum di Indonesia menjadi perhatian serius, terutama setelah terungkapnya kasus suap yang melibatkan tiga hakim Pengadilan Negeri Surabaya dalam perkara pembebasan terdakwa Ronald Tannur. Studi ini bertujuan untuk mengkaji bentuk pelanggaran etika dan kode etik profesi hukum yang terjadi, dampaknya terhadap integritas sistem peradilan dan kepercayaan publik, serta upaya pencegahan agar kasus serupa tidak terulang. Penelitian menggunakan metode hukum normatif dengan pendekatan studi pustaka, menganalisis sumber hukum primer dan sekunder yang relevan. Hasil kajian menunjukkan bahwa pelanggaran berupa penerimaan suap, konflik kepentingan, dan penyalahgunaan wewenang telah merusak prinsip keadilan, independensi, dan integritas peradilan. Dampak negatif yang timbul meliputi menurunnya kepercayaan masyarakat, melemahnya legitimasi lembaga peradilan, serta meningkatnya potensi korupsi sistemik. Penegakan kode etik yang tegas, penguatan mekanisme pengawasan internal dan eksternal, serta reformasi struktural dalam sistem peradilan menjadi langkah strategis yang diperlukan untuk memulihkan integritas dan profesionalisme aparat hukum di Indonesia, sekaligus memperkuat fondasi keadilan yang independen dan berintegritas bagi masyarakat luas.